Iowa Birdline update, January 28, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 28, 1989. Highlights include the sightings of a Great-tailed Grackle and a Snowy Owl along with updates on previously reported birds. Epson - sheet feed/flatbed